Use of Nitinol Shape Memory Alloy Staples (Niti Clips) after Cervical Discoidectomy: Minimally Invasive Instrumentation and Long-Term Results - Singh, D.; Sinha, S.; Singh, H.; Jagetia, A.; Gupta, S.; Gangoo, P.; Tandon, M. (min - Minimally Invasive Neurosurgery, 2011)
Anterior cervical discoidectomy with or without fusion is a well established surgical remedy for cervical prolapsed intervertebral disc (PIVD) disease. If fusion is done by an iliac bone graft then internal fixation is commonly used to keep the graft in position. This study was conducted to determine the efficacy and tolerability of shape memory alloys, especially NiTi (nickel titanium) clips in the stabilization of grafts following anterior cervical discoidectomy.133 NiTi clips were applied in 119 patients between January 2002 and December 2008. The patients age ranged from 38–60 years. There were 66 male and 53 females. Various indications for fixation of the spine included degenerated cervical spondylosis with single level PIVD (105) and two level PIVD in 14 patients. The cine mode fluoroscopy confirmed the perioperative correct placement of grafts and clips in all the patients. Follow-up ranged from 2 to 8 years (mean: 4.6 years).Single level discoidectomy was performed in 105 patients and two level disc removal was done in 14 patients. A single NiTi clip was applied in all the cases except for 14 cases of two level PIVD. No procedural complication or adverse reaction to the clip was noted. There was no movement at the operated level in dynamic lateral view X-ray of cervical spine at the 1st postoperative day as well as on follow-up. Graft extrusion was seen in one patient on the 2nd day after surgery and was reoperated. Bony fusion occurred in all patients after 9 − 12 months of surgery. There was no incidence of breakage or dislodgement of the clip from the site where it was inserted. No artifact was noted in cervical MRI done in 33 patients.NiTi clips are a simple alternative for cervical spine stabilization after discoidectomy. Their insertion is simple, minimally invasive, does not require any special set of instruments and they are much more economical than other established methods of treatment. These clips are accepted well by human tissue and do not interfere with MRI.
Keywords: minimal invasive spine surgery; spinal fusion; cervical fusion; NiTi; shape memory alloys